VARIATIONS OF INDONESIAN WORD FORMS DERIVED FROM THE TRANSLATION OF ENGLISH “RE–” PREFIXED WORDS - Gunawan Tambunsaribu; Fitri Amalia (DIALEKTIKA: JURNAL BAHASA, SASTRA DAN BUDAYA, 2026)
Translation presents various challenges, particularly in capturing the nuances of linguistic and morphological structures between languages, as translators must ensure that meaning, style, and cultural context are preserved while avoiding grammatical errors and inappropriate lexical choices. This study aims to identify and describe the Indonesian translations of English prefix “re-” words and analyze the morphological forms that express repetition or return. The significance of the study lies in bridging linguistic gaps, enhancing translation quality, and providing valuable resources for students, scholars, and general readers. Methodologically, this research employs a qualitative descriptive approach, using bilingual online news articles as the data source. The data were then analyzed using thematic analysis to examine both the equivalence and the similarities and differences in morphological forms between English “re-” words and their Indonesian translations. Keywords: morphological translation, linguistic equivalence, thematic analysis, qualitative descriptive research, bilingual corpus